2017
DOI: 10.1051/kmae/2016035
|View full text |Cite
|
Sign up to set email alerts
|

Ecological patterns of Odonata assemblages in karst springs in central Montenegro

Abstract: -Karstic springs are important habitats for maintaining freshwater biodiversity. However, little is known about Odonata larvae assemblages in karstic springs, and studies about the ecological factors that determine species distribution in these habitats are still lacking. In this study the composition of Odonata larvae communities from 91 springs located in the central part of Montenegro was investigated. The richest fauna was found in sublacustrine springs, followed by limnocrenes, while that of the rheocrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…This study confirmed that there is a strong relationship between distribution of freshwater benthic organisms and water temperature, dissolved oxygen concentration, nutrients, water velocity and substrate type (Corbet, 1964;Giller and Malmqvist, 1998;Moog, 2002;Allan and Castillo, 2007). In accordance with their previously recorded preferences for environmental factors (Corbet and Brooks, 2008;Pe sić et al, 2017), dragonfly larvae of the Plitvice Lakes hydrosystem favored habitats with higher water temperature, i.e. tufa barriers.…”
Section: Discussionsupporting
confidence: 88%
“…This study confirmed that there is a strong relationship between distribution of freshwater benthic organisms and water temperature, dissolved oxygen concentration, nutrients, water velocity and substrate type (Corbet, 1964;Giller and Malmqvist, 1998;Moog, 2002;Allan and Castillo, 2007). In accordance with their previously recorded preferences for environmental factors (Corbet and Brooks, 2008;Pe sić et al, 2017), dragonfly larvae of the Plitvice Lakes hydrosystem favored habitats with higher water temperature, i.e. tufa barriers.…”
Section: Discussionsupporting
confidence: 88%
“…Spring group C includes most of the modified springs of the study area. The construction of cribs leads to the transformation of these environments into semi‐lotic habitats, often with the formation of still water areas and the accumulation of organic material (Pešić et al, ). This probably explains the relationship between the indicator species mentioned and hydromorphological alteration.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of human‐induced environmental changes are evident for many springs in the Dinaric karst. Ecohydrological analyses of macroinvertebrate data have identified the modification of springs for drinking water supply or for aesthetic reasons as an important determinant of the composition of macroinvertebrate assemblages in springs (Lencioni, Marziali, & Rossaro, ; Pešić, Dmitrović, Savić, & von Fumetti, ; Pešić, Gligorović, Savić, & Buczyński, ; Płóciennik, Dmitrović, Pešić, & Gadawski, ; Savić et al, ). In general, the mode of modification when tapping a spring depends on the natural characteristics of a spring, especially its discharge (Stevanović, ).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular importance is the role of anthropogenic disturbance and how it affects the insects. Because Odonata are sensitive to disturbance, they are often considered good indicators of environmental quality (Samways and Steytler 1996, Kutcher and Bried 2014, Valente-Neto et al 2015, Pešić et al 2017. Given the well documented patterns of land use and anthropogenic disturbance in Puerto Rico, further research on this area is encouraged.…”
Section: Zygoptera -Coenagrionidaementioning
confidence: 99%